Preliminary Notes on Mantigue Island Capture Fisheries : Implicatons of a Marine Reserve - Maypa, Aileen P.; Alcala, Angel C.; Russ, Gary R. (Silliman Journal, 2022)
Marine reserves are often advocated as tools for sustainable fishery management. However, evaluation techniques on the effectiveness of established reserves are few. Although the Before-After-Control-Impact Pair (BACIP) experimental designs are most appropriate in detecting marine reserve impacts, they are rarely used. This study reports the first part of the BACIP results for Mantigue Island fishery yield. Based on daily roving creel surveys total estimated yield of the reefIseagrass fishery for 2000 was 4.88 tlkm21yr. Reef associated fish yield is 0.82 a km21yr and non-reef is 5.76 akm21yr. Of the 42 fish families caught, Belonidac (42%), Scaridae (10.3%), Engraulidae (7.6%), Labridae (7.28%) and Caesionidae (4.77%) dominated the annual catch. Four fishing gears were used in Mantigue: gill net, spear gun, hook and line and fish pots. Highest estimated total annual catch was also from gill nets, yielding 8.11 t of fish. Reef-associated fish catch per unit effort was significantly higher compared to reeflseagrass and non-reef catches but catch was lower than non-reef Low reeflseagrass fish yield and data on fish lengths of some species caught suggest that the reefiseagrass fisheries of Mantigue Island may have reached growth overfishing. If unsustainable fishing practices are continued, further degradation of fishery resources may move up to the higher levels of overfishing. Immediate management action is therefore essential. Establishment of a marine reserve in the area is now being undertaken through community based management. With BACIP used as the experimental design, the impacts of the Mantigue I. marine reserve on its fishery will be readily quantified over time.